2010
DOI: 10.3109/10641961003667922
|View full text |Cite
|
Sign up to set email alerts
|

Use of Home Blood Pressure Monitoring and Exercise, Diet and Medication Compliance in Japan

Abstract: Little is known about the attitudes of doctors and patients to the use of home blood pressure monitoring (HBPM) and its relationship with compliance to exercise, diet, and antihypertensive medication and blood pressure (BP) control. We conducted a cross-sectional internet survey in treated patients with hypertension in Japan. Overall, 500 questionnaires were returned; 292 respondents (58.4%) reported that their doctor had recommended HBPM and among them 106 (36.3%) reported satisfactory adherence to HBPM. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
7
2
1
Order By: Relevance
“…A qualitative study done in Malaysia found that patients who self-monitored were eager to be more involved in discussions about their blood pressure control 21. Similar findings were also reported in a qualitative study looking at primary care patients’ experiences of home blood pressure measurement in the United Kingdom and Japan 22,23. Therefore, wherever feasible, patients should be taught to measure and monitor their own blood pressure and to assess their own adherence.…”
Section: Discussionmentioning
confidence: 56%
“…A qualitative study done in Malaysia found that patients who self-monitored were eager to be more involved in discussions about their blood pressure control 21. Similar findings were also reported in a qualitative study looking at primary care patients’ experiences of home blood pressure measurement in the United Kingdom and Japan 22,23. Therefore, wherever feasible, patients should be taught to measure and monitor their own blood pressure and to assess their own adherence.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, interviewed patients reported an increased adherence to pharmacological and non-pharmacological method of hypertension management when they noted high blood pressure readings on their home blood pressure monitors. A recent study on the use of HBPM in Japan reported that patients who used HBPM regularly are more likely to have satisfactory compliance with exercise diet and medications [20]. …”
Section: Discussionmentioning
confidence: 99%
“…La búsqueda de la información le permite al paciente conocer y manejar su enfermedad y desempeñar un papel activo en su autocuidado, logrando la adherencia al tratamiento farmacológico y no farmacológico (21,22), de forma que el conocimiento del tratamiento farmacológico se constituye en una directriz que permite mejorar la calidad de vida, reducir complicaciones y la progresión de la enfermedad (23). Lograr que el paciente use adecuadamente la sal en su dieta es indicador de una apropiada información y comprensión, puesto que los estudios han mostrado que una de las mayores dificultades en el manejo de la hipertensión arterial es el uso adecuado de sal, debido a que una reducción de sodio puede disminuir 3,9 mm/Hg la presión sistólica y 1,9 mm/Hg la presión diastólica (13).…”
Section: Discussionunclassified